Monitoring and Evaluation Analysis of the Biomedical Science 1 Block: Misalignment between Formative and Summative Assessments among Medical Students at Universitas X in Bali - Mayun Putra; Putu Asih Primatanti; Putu Anastasia Kharisma; Robin Martilo Djajadi; Christine Rosalina Butar Butar (LPPM Universitas Dhyana Pura, 2026)
Abstract Biomedical science serves as the fundamental foundation of medical education, bridging the understanding of basic sciences with clinical reasoning. In competency-based curricula, formative assessment is designed to support the learning process and prepare students for summative evaluation. However, during the early phase of medical education, discrepancies between formative and summative assessment outcomes are still frequently observed and may reflect problems related to constructive alignment and the implementation of block-based learning. This study aimed to analyze the discrepancy between formative and summative assessments in the Biomedical Science 1 Block and to examine contributing factors based on Monitoring and Evaluation (Monev) findings. This study employed a mixed-methods design with an explanatory sequential approach. Quantitative analysis was conducted on the formative and summative assessment scores of 36 first-year medical students in the Medical Education Program at Universitas X during the Biomedical Science 1 Block (Anatomy, Histology, and Physiology) in the odd semester of the 2025/2026 academic year. Descriptive and comparative statistics were used to describe score distribution, pass rates, and discrepancies in learning achievement. Qualitative data were obtained from structured monitoring and evaluation reports involving block coordinators, lecturers, tutors, and the Quality Assurance Unit, and were subsequently analyzed. Data integration was performed during the interpretation phase. The results demonstrated a significant discrepancy between formative and summative assessments. Although most students achieved high formative assessment scores, only 12 out of 36 students (33.3%) passed the summative examination. The disparity in score distribution indicated the low predictive value of formative assessments. Monitoring and evaluation findings identified several contributing factors, including weak constructive alignment, less challenging formative assessment design, and high cognitive load. This study suggests that discrepancies between formative and summative assessments may serve as one of the indicators in learning monitoring and evaluation to identify potential problems in the implementation of block-based learning during the early phase of medical education.